1959
DOI: 10.1002/j.1537-2197.1959.tb07059.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Differentiation of Neurospora Hyphae

Abstract: Zalokar, Marko. (Yale U., New Haven, Conn.) Growth and differentiation of Neurospora hyphae. Amer. Jour. Bot. 46(8): 602–610. Illus. 1959.—Neurospora hyphae grow only at their tips. New protoplasm is formed throughout the hyphae and transported to the tips by active cytoplasmic streaming. This enables the fungus to grow at a prodigious rate. The use of radioactive precursors demonstrated that the rate of protein and ribonucleic acid formation does not decrease substantially in hyphal regions distant from the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

1970
1970
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(12 citation statements)
references
References 14 publications
0
9
0
3
Order By: Relevance
“…The volume fraction of cytoplasm occupied by mitochondria is highest 5-15 m behind the tip, which was also observed in Neurospora crassa (Lew, 1999). Zalokar (1959) mapped the distribution of mitochondria and mitochondrial biochemical activity in Neurospora, and found that, while mitochondria are located throughout the hyphal apical region (0-150 m), cytochrome oxidase and succinic dehydrogenase, which were identiWed histochemically, are Wrst observed 50 m behind the tip, and increase to a maximal level 100-150 m behind the tip. Of necessity, Zalokar's measurements required Wxation, which may alter the natural distribution of mitochondria.…”
Section: Introductionmentioning
confidence: 67%
“…The volume fraction of cytoplasm occupied by mitochondria is highest 5-15 m behind the tip, which was also observed in Neurospora crassa (Lew, 1999). Zalokar (1959) mapped the distribution of mitochondria and mitochondrial biochemical activity in Neurospora, and found that, while mitochondria are located throughout the hyphal apical region (0-150 m), cytochrome oxidase and succinic dehydrogenase, which were identiWed histochemically, are Wrst observed 50 m behind the tip, and increase to a maximal level 100-150 m behind the tip. Of necessity, Zalokar's measurements required Wxation, which may alter the natural distribution of mitochondria.…”
Section: Introductionmentioning
confidence: 67%
“…Growth of a non-budding strain of C. ulbicuns in sulphur-deficient medium stimulated budding and it was suggested that low availability of sulphur gave greater plasticity to the cell wall. Only a few -SH groups were found in the walls of fungi that form mycelia (Robson & Stockley, 1962) but more were observed near the hyphal tips (Zalokar, 1959; Robson & Stockley, 1962). Pitt (1969) found -SH groups near the tips of phialides of Penicillium notutum but none was detected elsewhere in the walls of this species.…”
Section: (C) the Possible Role Of Sulphur Bondsmentioning
confidence: 99%
“…This suggests that only mycelium formed in the presence of excess tryptophan is conditioned, at a later stage of development, to a high level of alkaloid synthesis. Although the effect might be attributed to a difference in nutrient uptake between older hyphae and growing tips, studies with other fungi (5,6,36,37) have indicated little distinction between different parts of the mycelium in assimilation and metabolism of amino acids. Tryptophan appears to be taken up readily by growing or resting mycelium of Claviceps strain HLX 123.…”
Section: Discussionmentioning
confidence: 94%